Whole-Genome Resequencing of Twenty Branchiostoma belcheri Individuals Provides a Brand-New Variant Dataset for Branchiostoma. (26th January 2020) - Bi, Changwei; Lu, Na; Han, Tingyu; Huang, Zhen; Chen, J.-Y.; He, Chunpeng; Lu, Zuhong
Abstract : As the extant representatives of the basal chordate lineage, amphioxi (including the genera Branchiostoma, Asymmetron and Epigonichthys ) play important roles in tracing the state of chordate ancestry. Previous studies have reported that members of the Branchiostoma species have similar morphological phenotypic characteristics, but in contrast, there are high levels of genetic polymorphisms in the populations. Here, we resequenced 20 Branchiostoma belcheri genomes to an average depth of approximately 12.5X using the Illumina HiSeq 2000 platform. In this study, over 52 million variations (~12% of the total genome) were detected in the B. belcheri population, and an average of 12.8 million variations (~3% of the total genome) were detected in each individual, confirming that Branchiostoma is one of the most genetically diverse species sequenced to date. Demographic inference analysis highlighted the role of historical global temperature in the long-term population dynamics of Branchiostoma, and revealed a population expansion at the Greenlandian stage of the current geological epoch. We detected 594 Single nucleotide polymorphism and 148 Indels in the Branchiostoma mitochondrial genome, and further analyzed their genetic mutations. A recent study found that the epithelial cells of the digestive tract in Branchiostoma can directly phagocytize food particles and convert them into absorbable nontoxic nutrients using powerful digestive and immune gene groups. In this study, we predicted all potential mutations in intracellular digestion-associated genes. The results showed that most "probably damaging" mutations were related to rare variants (MAF < 0.05) involved in strengthening or weakening the intracellular digestive capacity of Branchiostoma . Due to the extremely high number of polymorphisms in the Branchiostoma genome, our analysis with a depth of approximately 12.5X can only be considered a preliminary analysis. However, the novel variant dataset provided here is a valuable resource for further investigation of phagocytic intracellular digestion in Branchiostoma and determination of the phenotypic and genotypic features of Branchiostoma .